A facile synthesis of soluble polyimides with high glass transition temperature and excellent mechanical properties due to intermolecular hydrogen bonds. (April 2020) - Li, Ke; Zhou, Lan; Wu, Simin; Yu, Qiyu; Yang, Long
An unsymmetrical heterocyclic diamine monomer containing proton donor (–NH–), 2-(4-aminophenyl)-5-aminobenzimidazole (PABZ), which can form hydrogen bond interactions with carbonyl functional group, was copolymerized with 4, 4′-(hexafluoroisopropylidene)diphthalic anhydride (6FDA) and 2, 2′-bis(trifluoromethyl)-4, 4′-diaminobiphenyl (TFMB) through two-step synthetic methods to obtain a series of homo- and co-polyimide (PI). The corresponding homo- and co-PI both exhibited good solubility in aprotic polar solvents, such as N, N -dimethylacetamide, N -methyl-2-pyrrolidone, N, N -dimethylformamide, pyridine, and dimethyl sulfoxide. In addition, the PI-containing PABZ units showed excellent tensile strength ranging from 83 to 164 MPa, 130–260% higher than 6FDA/TFMB homo-PIa films. These PIs, especially PABZ/6FDA, showed very high glass transition temperatures, 430°C.